Exploring the Effectiveness of the Flipped Classroom as a Teaching Strategy for Improving Student Learning - Archibald, Gail (My University, 2016)
This research is driven by a lack of student engagement, with content and peers, specifically in a third year business management module. Linked to this, the purpose of this article is to present the findings from research conducted into the value of adopting a ‘flipped classroom’ teaching approach, in higher education, with the intention of enhancing student engagement which Strydom, Metz and Kuh (2010) have identified as an attributing factor to student success. The research follows an interpretivist approach in an attempt to understand student behaviour and determine whether the ‘flipped classroom’ approach improves student engagement, leading to better information retention and recall. Findings reveal that the students, from the sample population, found the elements of the flipped classroom both entertaining and engaging and revealed that their understanding of content was deepened and their ability to retain and apply information was heightened through the various elements of the flipped classroom.
Keywords: Flipped classroom; Student engagement; Interpretivist approach; Higher education